Nutrient Cycling Index in Relation to Organic Matter and Soil Respiration of Rehabilitated Mine Sites in Kelian, East Kalimantan - Dwi Setyawan; Robert Gilkes; David Tongway (JOURNAL OF TROPICAL SOILS, 2011)
Degraded soils at mine sites are often associated with decreased soil fertility.  However, soil nutrient status might be improved through biomass recovery primarily from re-vegetation.  This paper relates nutrient cycling index (NCI) derived from Landscape Function Analysis (LFA) to soil respiration and soil organic matter as a measure of improving soil condition after rehabilitation.  Fieldwork was conducted at Kelian Equatorial Mining, East Kalimantan in June 2001.  Four sites were selected representing rehabilitation work in 1994 (7 year), 2000 (1 year) and 2001 (3 month), and a reference site of undisturbed primary forest.  The NCI value was calculated from scores of basal/canopy cover, litter (abundance, origin and degree of incorporation), cryptogam cover and surface roughness.  Soil respiration was measured using the inverted-box method.  In general, the NCI values increased with age of rehabilitation (12 to 56 %) showing a significant increase compared with the values of reference site (80%).  Soil respiration varied greatly and the values were equally high (200-800 mg CO2 m-2 hr2) across all sites. Tropical soils like those of Kelian might be inherently rich of soil organism as shown by high value of soil respiration.  Nevertheless, the NCI values were not systematically related to soil respiration.  We found that increased organic matter may be used as early sign of functioning soil resources in degraded land.